2003
DOI: 10.1016/s0735-1097(02)02967-4
|View full text |Cite
|
Sign up to set email alerts
|

Age and hemodynamic responses to tilt testing in those with syncope of unknown origin

Abstract: There appear to be distinct pathophysiologies underlying vasovagal syncope in different age groups. Young people appear to have excessive cardiac and autonomic responses to stress, whereas older patients appear to have a more generalized cardiovascular decline, with attenuated cardiac and autonomic responses to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 18 publications
6
29
0
Order By: Relevance
“…Age is an important factor. Similar to others [11], and consistent with the age-related reduction in vagally mediated physiological phenomena, such as respiratory sinus arrhythmia [13], we found a trend of progressively less pronounced bradycardia during vasovagal syncope with advancing age: patients with type III vasodepressor syncope in the VASIS classification [16] were older than those with more pronounced bradycardia, classified as type IIA and IIB of the VASIS classification (30 ± 6 vs. 51 ± 5 years, P \ 0.05).…”
Section: Discussionsupporting
confidence: 87%
“…Age is an important factor. Similar to others [11], and consistent with the age-related reduction in vagally mediated physiological phenomena, such as respiratory sinus arrhythmia [13], we found a trend of progressively less pronounced bradycardia during vasovagal syncope with advancing age: patients with type III vasodepressor syncope in the VASIS classification [16] were older than those with more pronounced bradycardia, classified as type IIA and IIB of the VASIS classification (30 ± 6 vs. 51 ± 5 years, P \ 0.05).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, our results of a decrease in BRG with age could be explained by either the presence of a blunted efferent cardiovagal response of the reflex arc or intrinsic sinus node disease [21]. Our findings of the relationship between age and type of tilt response are aligned with the work of Kurbaan et al who showed that age was associated with greater prevalence of a vasodepressor response in older patients (>65 years; OR 29.5, p <0.0001) [24].…”
Section: Present Studysupporting
confidence: 89%
“…The authors found that patients with ages 31-50 years and >50 years old had a lower increase in HR during the first 20 minutes of tilt table testing when compared to patients younger than 30 years old. In another study by Kurbaan et al, the authors made a similar observation that age was associated with blunted HR response when compared to younger patients (OR 1.04, p<0.0002) [24]. Therefore, the observed blunted HR response might very well be related to age although its role in determining outcome remains unclear.…”
Section: Present Studymentioning
confidence: 83%
“…17) Some previous studies regarded head-up tilt testing as the endpoint and thus obtained a distinctively different or even opposite conclusion. 18,19) This may be due to differences in the diagnostic tilt testing protocol. Some positive results can only be obtained by pharmacological stimulation, and thus the specificity of head-up tilt testing is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Some positive results can only be obtained by pharmacological stimulation, and thus the specificity of head-up tilt testing is greatly reduced. 19) Moreover, repeat tilt testing for diagnostic purposes may have a limited role. Once patients have been tilted, their responses may change because they are aware of what to expect and attempt to respond.…”
Section: Discussionmentioning
confidence: 99%